Description of two new species of bathyal Primnoidae (Octocorallia: Alcyonacea) from the Porcupine Bank (northeastern Atlantic) - Altuna, Álvaro; López-González, Pablo J. (Zootaxa, 2019)
Two new species of bathyal Primnoidae gorgonians (Octocorallia: Alcyonacea), Callogorgia europaea sp. nov., and Thouarella porcupinensis sp. nov., were collected during a research expedition of the Spanish Institute of Oceanography to the Porcupine Bank (off Ireland, northeastern Atlantic). In the present paper, both species are described, compared with their closest congeners, and their polyps and scleromes illustrated by scanning electron microphotographs. Callogorgia europaea sp. nov. is the first species of the genus described from the northeastern Atlantic having abaxial scales with an external ornamentation of prominent longitudinal crests. Thouarella porcupinensis sp. nov. is the first one in the same area characterized by a planar ramification with isolated polyps, and marginal scales having several perpendicular ridges in their distal inner side instead of a pointed edge.